Aneka Ragam Identitas Islam Dari Berbagai Perspektif - Andri Qurniawan; Ahmad Nurhuda; Hamid Abdillah; Restu Dwi Cahya (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
Variety is a variety of things, while identity is a sign of self-identification. With identity, we will be more easily recognized by others. Then when related to the word